Estrategias de afrontamiento ante el duelo en adultos mayores del Centro Gerontológico de San Miguel de Bolívar - Lanchi Merchán, Kerly Ariana (2024)
The present research is descriptive in nature, with a cross-sectional non-experimental design, the sample consisted of 45 older adults from the gerontological center selected by non-probabilistic sampling by quotas. Through a Likert scale survey together with instruments such as the Revised Texas Grief Inventory and the Coping Strategies Scale - Modified, it was obtained that this population suffers a complicated grief, maintaining difficulties in the acceptance of death, and experienced persistent feelings of sadness, guilt, anger, frustration, among others. It was also recorded that the most used coping strategy is religion, most of the older adults practice prayers and prayers before the loss of a loved one. The type of coping strategy used by the older adult affects the type of grief experienced by this population, whether normal or pathological. The term grief comes from the Latin dolus which translated into Spanish means pain, challenge or combat; and, corresponds to that demonstration that shows the feeling that one has for any type of loss, the coping strategies are defined as the constant change of individual, cognitive or behavioral efforts, which exceed the capacity of the person. Likewise, the grieving process in older adults is important for their mental health and emotional well-being.